Comparison of the effects of biological and electrical stimulation on the growth of Zea mays. (20th April 2023) - Solís, S.; Contreras-Ramos, S.M.; Bacame-Valenzuela, F.J.; Reyes-Vidal, Y.; González-Jasso, E.; Bustos, E.
Highlights: Increase the growth of plants such as maize using biological and electrical stimulation. Electrical stimulation showed more increased maize growth than biological stimulation. IrO2-Ta2O5| Ti promotes the electrical stimulation of maize growth using 0.2 V cm−1 and 2 mA for 4 h. Electrical stimulation increases the amount of biomass: leaves, stem, and roots. Electrical stimulation promotes the movement of nutrients near of the roots of the plants by the electro-migration. Electrical and biological stimulation promotes the movement of bacteria and fungi by the electrophoresis. Abstract: As the current economic problems deepen while human populations continue to expand, hunger and malnutrition are likely to increase. Their eradication is one of the great challenges of our time. For this reason, it is important to look for technological advancements to accelerate plant growth and improve family economies throughout the world. A promising technique to increase the growth of plants such as maize is using biological and electrical stimulation. The first employs the inclusion of a consortium of microorganism into the soil, and the second uses the application of an electric field with at least one pair of electrodes inserted into the soil. In this study, our team compared biological and electrical stimulation individually and when coupled. Electrical stimulation with low intensity (0.2 V cm−1 and 2 mA) electrical field for 4 hours showed more increased maize growth, using electrodes with surfaces modified with transition metal oxides such as IrO2 -Ta2 O5 ΙTi Ti, when compared to the biological stimulation using a consortium of microorganisms, and a combination of electrical and biological stimulation. The electrical stimulation increases the amount of biomass (leaves, stem, and roots) for the plants germinated and allowed to grow for 14 days due to the greater availability of nutrients near of the roots of the plants as caused by the electro-migration of macro and micronutrients driven by the electric field. Graphical abstract: Image, graphical abstract